Antifungal, Antiaflatoxin and Antioxidant Activity of Plant Essential Oils and Their In Vivo Efficacy in Protection of Chickpea Seeds. Issue 1 (20th October 2015) - Prakash, Bhanu; Kedia, Akash; Singh, Aakanksha; Yadav, Shashi; Singh, Arti; Yadav, Amrita; Deepika,; Dubey, Nawal Kishore
Abstract: This study presents the efficacy of six essential oils (EOs), viz. C arum carvi, M yristica fragrans, M elaleuca leucadendra, C innamomum camphora, P elargonium odoratissimum and C ymbopogon citratus, as food preservatives based on antifungal, antiaflatoxin and antioxidant activity. The minimum inhibitory concentration of EOs against aflatoxigenic strain of A spergillus flavus (LHP‐10) and 13 other storage molds ranged between 1.25 and 6.0 μL/mL, while aflatoxin inhibition was observed at 1.0–5.0 μL/mL. EOs also exhibited free‐radical scavenging activity through DPPH (2, 2‐diphenyl‐1‐picrylhydrazil) assay as IC50 value ranged between 3.96 and 96.63 μL/mL. The antifungal action of EOs was observed in terms of reduction in ergosterol content of the plasma membrane of A . flavus . The EOs provided >50% protection of chickpea samples against fungal association without affecting their germination during in vivo testing in storage containers. Based on antifungal, antiaflatoxigenic, antioxidant potential and in vivo efficacy, the tested EOs may be recommended as plant‐based food preservatives. Practical Applications: Some safer alternatives are urgently required to replace prevalent synthetic preservatives that have adverse effects on consumer's health and environment. In that respect, some essential oils (EOs) have shown potency in the formulation of plant‐based preservatives against food deterioration from fungi. Based on the results of the present investigation, some EOs may be recommended as plant‐based preservatives in view of their antifungal potency against foodborne molds, aflatoxin secretion and as antioxidant. The EOs also showed efficacy in protecting chickpea seeds from fungal contamination during storage without affecting their viability, strengthening their formulation for practical application.